Persons with patellar tendinopathy exhibit anatomical features that alter knee extensor mechanics: A comparison of persons with and without symptoms - Park, K.; Salem, G.; Powers, C. M. (Journal of Biomechanics, 2022)
It has been postulated that anatomical features of the patellofemoral joint may alter knee extensor mechanics in a way that may contribute to excessive patellar tendon loading. The purpose of this study was to compare the knee extensor mechanics in persons with and without patellar tendinopathy. Twenty-eight individuals participated (14 with patellar tendinopathy and 14 pain-free controls). Sagittal magnetic resonance images of the knee were acquired at the knee flexion angle that corresponded to the knee flexion angle at the time of peak knee extensor moment during a single-leg landing task. Measurements of patellar tendon/quadriceps tendon force ratio, quadriceps moment arm, patellar tendon moment arm, and patellar height (Insall-Salvati ratio) were obtained. Independent t-tests were used to compare the variables of interest between groups. When compared to the control group, the patellar tendinopathy group exhibited significantly a greater patellar tendon/quadriceps tendon force ratio (Mean ± SD, 1.0 ± 0.1 vs 0.8 ± 0.1, p < 0.05), a larger quadriceps moment arm (Mean ± SD, 23.9 ± 2.0 mm vs 22.1 ± 2.9 mm, p < 0.05), a smaller patellar tendon moment arm (Mean ± SD, 24.2 ± 1.7 mm vs 26.3 ± 2.4 mm, p < 0.05) and a greater Insall-Salvati ratio (Mean ± SD, 1.2 ± 0.1 vs 1.1 ± 0.1, p < 0.05). These results suggest that persons with patellar tendinopathy may experience greater forces in the patellar tendon for a given level of quadriceps force.